2008 IEEE International Conference on RFID 2008
DOI: 10.1109/rfid.2008.4519370
|View full text |Cite
|
Sign up to set email alerts
|

EC-RAC (ECDLP Based Randomized Access Control): Provably Secure RFID authentication protocol

Abstract: Abstract-Operational and security requirements for RFID systems such as system scalability, anonymity and anti-cloning are difficult to obtain due to constraints in area, memory, etc. Due to scarceness of resources most of the proposed protocols were designed using symmetric key cryptographic algorithms. However, it has been shown that it is inevitable to use public-key cryptographic algorithms to satisfy these requirements [1]. Moreover, general public-key cryptography based authentication protocols are vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…There are some papers which propose to use PKC-based RFID systems [25], [22], [2], [11]. In [25] no specific authentication protocol is mentioned, and the Schnorr protocol [18] and the Okamoto protocol [16] are adopted in [22] and [2] respectively.…”
Section: Background and Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…There are some papers which propose to use PKC-based RFID systems [25], [22], [2], [11]. In [25] no specific authentication protocol is mentioned, and the Schnorr protocol [18] and the Okamoto protocol [16] are adopted in [22] and [2] respectively.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In [25] no specific authentication protocol is mentioned, and the Schnorr protocol [18] and the Okamoto protocol [16] are adopted in [22] and [2] respectively. However, it is shown that these two protocols are not proper for RFID systems due to their vulnerability against the tracking attack [11]. In [11] EC-RAC is also proposed to solve all the basic properties required in RFID systems.…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations